Curcumin supplementation in the treatment of patients with cancer: a systematic review (Brazilian Journal of Pharmaceutical Sciences, 2022)
Feeding with high levels of phytochemicals, including curcumin, may be a therapeutic option for diseases such as cancer which is a public health problem. The aim of this study was to systematically review the results of clinical trials investigating the effect of oral curcumin supplementation on anti-inflammatory and antioxidant profiles, reduction of PSA levels and degree of dermatitis in radiotherapy treatment in cancer patients. The review was carried out based on the items of the PRISMA Statement. A bias risk assessment was performed according to Cochrane Collaboration criteria. Six studies met the eligibility criteria and were included in the systematic review. The results of this study are based on those obtained in the literature on the effect of curcumin on the anti-inflammatory profile, on reducing dermatitis, on PSA alteration and on anti-oxidant profile for a total of 450 individuals, comprising 259 in the intervention group and 191 in the control group. Some studies have reported improvement in biochemical and clinical indicators, with limited adverse effects and good tolerance. It was not possible to determine, with the desired degree of evidence, the effect of curcumin supplementation in the treatment of cancer patients. It is important to consider the great heterogeneity and methodological weaknesses of the studies, and that it was not possible to perform a meta-analysis of the data available in the literature.